Perlindungan Hukum terhadap Pencipta Musik sebagai Suara Latar di Youtube - Komang Ariadarma Suputra; Ida Ayu Putu Widiati; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2020)
The use of music as video background sound is currently rife on social media Youtube. This is inseparable from the moral and economic benefits that users get through the features offered by Youtube. Therefore, as a state of law, Indonesia should appropriately provide legal protection for Music Creators whose works are used. The purpose of this study is to analyze the legal protection of music creators as a background voice on Youtube and find out the sanctions imposed on Youtube channels that commit copyright infringement. The research method used is normative legal research with statutory and conceptual approaches. The results showed that music is the result of human expression that has an element of beauty in it. Thus, the need for legal protection is given to the Creator. Legal protection is preventive, namely the formulation of the exclusive right of a Music Creator to Article 5 and Article 9 of Law no. 28 of 2014 concerning Copyright and repressively, the Music Creator can fight for his rights that have been violated through the courts and outside the court. As for the sanctions against violations of music copyright as the background sound of videos on Youtube, namely sanctions in the form of compensation for damages that have been caused as stipulated in Article 99 of Law No. 28 of 2014 concerning Copyright. Criminal sanctions are regulated in Article 113 paragraph (4) of Law no. 28 of 2014 concerning Copyright in the form of a maximum imprisonment of 10 years and / or a maximum fine of Rp. 4,000,000,000.00